Sam68 promotes self-renewal and glycolytic metabolism in mouse neural progenitor cells by modulating Aldh1a3 pre-mRNA 3'-end processing - Piergiorgio La Rosa; Pamela Bielli; Claudia Compagnucci; Eleonora Cesari; Elisabetta Volpe; Stefano Farioli Vecchioli; Claudio Sette (eLife, 2016)
The balance between self-renewal and differentiation of neural progenitor cells (NPCs) dictates neurogenesis and proper brain development. We found that the RNA- binding protein Sam68 (Khdrbs1) is strongly expressed in neurogenic areas of the neocortex and supports the self-renewing potential of mouse NPCs. Knockout of Khdrbs1 constricted the pool of proliferating NPCs by accelerating their cell cycle exit and differentiation into post-mitotic neurons. Sam68 function was linked to regulation of Aldh1a3 pre-mRNA 3'-end processing. Binding of Sam68 to an intronic polyadenylation site prevents its recognition and premature transcript termination, favoring expression of a functional enzyme. The lower ALDH1A3 expression and activity in Khdrbs1-/- NPCs results in reduced glycolysis and clonogenicity, thus depleting the embryonic NPC pool and limiting cortical expansion. Our study identifies Sam68 as a key regulator of NPC self-renewal and establishes a novel link between modulation of ALDH1A3 expression and maintenance of high glycolytic metabolism in the developing cortex.